Challenging Dilemma regarding Cardiac Advanced Life Support in Patients with Minimally Invasive Cardiac Surgery: A Letter to Editor - Hosseinzadeh Maleki, Mahmood; Yaghubi, Mohsen (Archives of Academic Emergency Medicine, 2025)
Cardiac Advanced Life Support (CALS) differs from conventional Advanced Cardiac Life Support (ACLS) in utilizing targeted resuscitation protocols designed explicitly for post-cardiac surgery patients. The hallmark of CALS is the performance of prompt re-sternotomy and internal cardiac massage within 5 minutes of cardiac arrest if the patient is unresponsive to external chest compressions and rapid defibrillation. The standardized algorithms for ACLS, fundamental to managing cardiac arrest, present a significant and potentially dangerous dilemma when applied to patients who have undergone minimally invasive cardiac surgery (MICS). While MICS offers benefits like reduced trauma and faster recovery, it creates a unique physiological landscape that conflicts with conventional resuscitation. This letter highlights the urgent need to re-evaluate the ACLS protocol for this growing patient population. We advocate for the immediate development of a specialized MICS-specific resuscitation guideline that moves beyond a one-size-fits-all approach to in-hospital cardiac arrest.